2011
DOI: 10.1111/j.1365-2982.2011.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of histamine receptors and effects of histamine on murine and simian colonic excitability

Abstract: Background Inflammatory responses can include recruitment of cells of hematopoietic origin to the tunica muscularis. These cells can secrete a variety of factors which can reset the gain of smooth muscle cells (SMC) and influence motor patterns. Histamine, a major mediator in inflammation, is released by mast cells and exerts diverse effects in SMC by binding to histamine (H) receptors. The profiles of H receptor expression in animal models used to study inflammatory diseases are unknown. Methods H receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…To identify the receptor subtypes of histamine involved in cultured ICCs, cells were treated with various histamine receptor agonists. 2-Pyridylethylamine (2-PEA) (a selective H1-agonist) [26], Dimaprit (a selective H2-agonist) [24], R-alpha-methylhistamine (R-alpha-MeHa) (a selective H3-agonist) [24], and 4-methylhistamine (4-MH) (a selective H4-agonist) [27] were all administered at a concentration of 50µM. 2-PEA depolarized pacemaker potentials, but others histamine receptor agonists had no effects on pacemaker potentials (n=5, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To identify the receptor subtypes of histamine involved in cultured ICCs, cells were treated with various histamine receptor agonists. 2-Pyridylethylamine (2-PEA) (a selective H1-agonist) [26], Dimaprit (a selective H2-agonist) [24], R-alpha-methylhistamine (R-alpha-MeHa) (a selective H3-agonist) [24], and 4-methylhistamine (4-MH) (a selective H4-agonist) [27] were all administered at a concentration of 50µM. 2-PEA depolarized pacemaker potentials, but others histamine receptor agonists had no effects on pacemaker potentials (n=5, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bolton et al [38] showed that histamine depolarized longitudinal smooth muscle cells and increased action potential discharge in guinea-pig ileum. Recently, Kim et al [24] investigated that H1, H2 and H4 receptor transcripts were expressed at similar levels in simian colonic tissue whereas only the H2 receptor transcript was detected in murine colonic tissue. Stimulation of simian colonic muscles with histamine caused depolarization and contraction in the presence of TTX.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations